A Study of Cloud Computing Based on Virtualization and Security Threats - Kaur, Amanpreet; Singh Khurmi, Sawtantar (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an emerging technology based on the network that provides access to the data from server. It Cloud computing is an emerging technology based on the network that provides access to the data from server. It illustrates an extremely scalable computing asset offered as an external service Paid by Internet method. In cloud computing, mainly we have focused on virtualization, energy efficiency and security. In this paper, we conducted a survey of cloud computing which is a framework that uses different services, IaaS, PaaS, SaaS and HaaS. A comparison for the same is also explained. The concept of virtualization is also discussed following Bare metal hypervisor, Hosted hypervisor and VMM (Virtual machine migration). Different security threats have been mentioned being considered for cloud services. For the calculation of energy consumption, cloud computing uses energy efficiency concept. Work done by various authors in cloud computing has been discussed with the research gap as well.